Risk Factors for a Long Hospital Stay Following Minimally Invasive Lumbar Discectomy. Issue 1 (February 2019) - Khechen, Benjamin; Haws, Brittany E.; Patel, Dil V.; Narain, Ankur S.; Hijji, Fady Y.; Bawa, Mundeep S.; Cardinal, Kaitlyn L.; Guntin, Jordan A.; Singh, Kern
Abstract : Study Design: Retrospective cohort study. Objective: The purpose of the study was to determine risk factors for discharge after postoperative day (POD) 0 in patients undergoing 1-level minimally invasive lumbar discectomy (MIS LD). Summary of Background Data: MIS LD has proven to be an effective treatment modality for low back pain and radiculopathy associated with intervertebral disc herniations. With increasing focus on cost reduction and value-based care, minimization of postoperative length of stay has become an important topic for physicians and hospital administrators. Methods: A prospectively maintained surgical database of patients who underwent 1-level MIS LD by a single surgeon from 2011 to 2016 was reviewed. Long length of stay was defined as discharge after POD 0. Bivariate and stepwise multivariate Poisson regression with robust error variance was used to determine risk factors for discharge after POD 0. Variables analyzed included patient demographics, comorbidities, operative characteristics, preoperative pain scores, postoperative inpatient pain scores, and postoperative narcotics consumption. Results: A total of 176 patients were included; 9.7% of included patients were discharged on POD 1 or later. On bivariate analysis, diabetic status (57.1% vs. 7.7%; relative risk [RR]=7.43; P <0.01) and narcotic consumption <6.00 oral morphine equivalents/h (13.1% vs. 1.2%; RR=11.11; P =0.019) were associated with a prolonged length of stay. On stepwise multivariate analysis, diabetic status (RR=10.5; 95% confidence interval, 3.60–30.98; P <0.001) was found to be independently associated with a prolonged length of stay after MIS LD. Conclusions: The results indicate that diabetic status is an independent risk factor for increased LOS following single-level MIS LD. Delayed hospital discharge can lead to increased costs, increased risk of complications, and decreased patient satisfaction. Thus, providers can use this information to better counsel diabetic patients and monitor them more closely following MIS LD. Additional work must be done to better understand risk factors for increased length of stay following MIS LD in procedure-specific populations. Level of Evidence: Level II.